The Influence of Patient Factors on Medication Adherence in Ambulatory Care Unit at Bangplama Hospital, Suphanburi - Tantipiwattanasakul, Kamolwan (Journal of Health Science of Thailand, 2019)
Medication adherence is associated with quality of life, morbidity, mortality and hospitalization of patients. Pharmacist can provide the influential role to enhance medication adherence. Determination of patient factors means the successful key for drug related problems (DRPs) management. The purpose of this study was to determine the DRPs and patient factors affecting on medication adherence. The study site was an ambulatory care unit at Bangplama Hospital, Suphanburi Province. Retrospective data were gathered from 212 patients in warfarin clinic, asthma clinic, and diabetes mellitus clinic in the fiscal year of 2015. Total of 394 DRPs were detected. The most important DRP was non-compliance problem. It was counted for 205 problems (52.03%). The influence of patient factors was different among three special clinics. Three patient factors were significantly associated with non-adherence. They were patient aged over 60 years old (p=0.007), unscheduled appointment (p=0.001), and cardiovascular co-morbidity (p=0.039). If the therapeutic target was accomplished, such as controlled asthma symptoms, targeted fasting blood sugar level and targeted INR, it would be significantly associated with the decrease of non-adherence (p=0.001). Patients’ caregiver was also helpful to improve their adherence (p=0.026). The results from this study could provide information on medication adherence for pharmacy department and patient care team. Pharmaceutical care activity should give priority to the elderly patients without caregiver or to the patients with chronic diseases or those who failed to follow-up the treatment. As a result, the efficacy and safety of pharmacotherapy could be improved.